Respiratory infection promotes T cell infiltration and Aβ deposition in APP/PS1 mice. - MCMANUS, ROSS; LYNCH, MARINA; MILLS, KINGSTON (My University, 2014)
Alzheimer?s disease (AD) is a progressive neurodegenerative disease characterized by deposits of amyloid-? and neurofibrillary tangles. It has been suggested that inflammatory changes are associated with disease; however, it has not been established if these are a consequence of ongoing neurodegeneration or whether inflammation itself contributes to disease pathogenesis. Recent studies suggest that exposure to infection can accelerate cognitive decline in AD patients, and pathogens have been detected in the AD brain. However, the influence of infection on neuroinflammation and pathology remains poorly understood. In this study, we examined the effect of a peripheral infection on AD pathology in APP/PS1 mice. We found that, 8 weeks after infection with the Gram negative respiratory pathogen Bordetella pertussis, there was significant infiltration of IFN?- and IL-17-producing T cells and NKT cells in older APP/PS1 mice. This was accompanied by increased glial activation and amyloid ? deposition. The data suggest that infection is a critical factor in the progression of AD, emphasising the importance of early diagnosis and treatment of infections in elderly individuals.
PUBLISHED
Keywords: Alzheimer?s disease, infection, T cell, microglia, amyloid ?, neuroinflammation; Alzheimer?s disease, infection, T cell, microglia, amyloid ?, neuroinflammation; Immunology, Inflammation & Infection; Neuroscience